Digitalisation, innovation, and transformation : 18th IFIP WG 8.1 International Conference on Informatics and Semiotics in Organisations, ICISO 2018, Reading, UK, July 16-18, 2018, Proceedings /: 18th IFIP WG 8.1 International Conference on Informatics and Semiotics in Organisations, ICISO 2018, Reading, UK, July 16-18, 2018, Proceedings. (2018) - Unknown
No abstract available